Laser-assisted synthesis of Au aerogel with high-index facets for ethanol oxidation. (28th May 2022) - Zhu, Jiayin; Zhang, Ran; Zhu, Liye; Liu, Xuan; Zhu, Tiying; Guo, Ziang; Zhao, Yan
Abstract: Gold (Au) can be used as an ideal metal electrocatalyst for ethanol and glucose oxidation reactions due to its high performance-to-cost ratio. In this paper, the Au aerogel with high-index facets was synthesized by using the laser ablation in liquid technology, which can improve the electrocatalytic activity of Au. The as-prepared Au aerogel showed excellent mass activity and specific activity toward ethanol oxidation reaction, which are 4.6 times and 2.1 times higher than Au/C, respectively. The 3D porous nature and rich defect of the Au aerogel provide more active sites. In addition, the high-index facets with under-coordinated atoms enhance the adsorption of ethanol and glucose molecules, thus improving the intrinsic catalytic activity of Au aerogel. The effect of high-index facets has also been investigated by density functional theory calculations. Furthermore, the Au aerogels also show good electrocatalytic activity and stability toward glucose oxidation reaction. These results are conducive to promote the practical application of Au in electrocatalysis.